Myanmar: the ties between health and democracy - Clelia D'Apice; Leopoldo Sarli; Zaw Wai Soe (Inishmore Laser Scientific Publishing Ltd, 2021)
In this viewpoint, we examined the ongoing crisis of the Myanmar health system following the military takeover of 1 February 2021, the health challenges faced by the population, and the tragic conditions in which the health professionals find themselves. We describe the efforts undertaken by representatives of the democratic health and university institutions to create the conditions for a resumption of the call for peace throughout the country and strengthen the resilience of the health system. In particular, we present the interim health service strategy devised by the Myanmar Ministry of Health (MOH), as appointed by the democratic government. The MOH's plan represents the entry point to use health as a bridge for peace and restoration of democracy and human rights, showing that the health sector of a country can be reshaped and revitalized in times of great adversity.